Pengembangan Media Penilaian Gerak Dasar Lokomotor Berbasis Aplikasi dan Permainan Balok Susun Untuk Anak Usia 7-9 Tahun - Muhammad, Alawy; Novitasari, Eka Fitri; Irawan, Andri (Advances In Social Humanities Research, 2023)
The purpose of this research and development is to modify the basic locomotor movement assessment device with blocks as media for children aged 7-9 years. This research and development uses a quantitative approach and uses the Research and Development method with the ADDIE model. The subjects in this research and development are children aged 7-9 years. The instruments used in this study were interviews and basic locomotor movement instruments and media used at the following stages: (1) needs analysis (2) media design (3) media development (4) field implementation (5) product evaluation. The results of the validation test were carried out with three experts. The results of validation with learning media experts had very good interpretations with an average score of 95.5%, while the results of validation with basic motion experts had very good interpretations with an average score of 93.3%, and the results of validation with learning media experts had very good interpretations with an average score of 95.5%. This explains that the development of basic locomotor motion instruments based on stacking blocks for children aged 7-9 years is feasible to try out and to form basic locomotor movements and assist assessment. Based on the results development it can be concluded that: (1) by developing locomotor basic movement assessment instruments based on stacking blocks for children aged 7-9 years can train basic locomotor movement abilities for children aged 7-9 years (2) generate enthusiasm and (3) make it easier for teachers to carry out locomotor basic movement assessments for children aged 7-9 years.